(untitled) (Global Journal of Human-Social Science, 2014)
This study examines the context of conflict resolution in Benin during the pre-colonial period. It seeks to transcend the often emphasised explanation concerning conflicts in Africa in terms of social antagonism, rather, it examines the political, social and economic institutions of pre-colonial Benin to demonstrate the point that development in Africa as emphasised by some European writers were not the product of European presence in the continent of Africa. The study employed the historical method of collection and interpretation of data in its analysis. The study found that prior to the coming of Europeans, Benin like other states of West Africa, had its indigenous mechanisms for conflict resolution and thus contributes to the debate as to whether African states owed their existence with regards to socio-political and economic organisation to European presence or not.